Analisis Self-directed Learning (SDL) Mahasiswa dan Partisipasi Dukungan Institusi sebagai Faktor Eksternal: Studi Kasus pada Politeknik Palu Sulawesi Tengah - , AKMA IL FAJRIN; , Prof. dr. Harsono, Sp.S (k) ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Changes in learning paradigm centered on learners who applied to college students as well as the conception of adult learners (adult learning), giving demands of the role that must be carried by the faculty as a delivery system and a means of support, while students have a proactive attitude and self-directed learning. One of the colleges that support the development of this role is the Polytechnic Palu, Central Sulawesi, which has been providing a range of support for the creation of student self-directed learning. However, in order to evaluate the actions and development institutions do not yet have data describing the extent to which performance goals are obtained (the level of self-directed learning) and the extent to which a given function support (support participation rate). The purpose of research to assess the level of self-directed learning (SDL) and the level of student participation institutional support for SDL, as well as testing the significance of the relationship between these two aspects of the Polytechnic Palu, Central Sulawesi. The method in this study using cross sectional study with a quantitative approach. Data processing was performed by descriptive and inferential statistics. Data were collected by questionnaire and a questionnaire SDL support at the 120 level student participation based on inclusion and exclusion criteria (primary data), as well as the questionnaire support the participation rate at 43 professors and officials (secondary data) Polytechnic Palu, Central SulawesiResearch shows students at the level of the SDL obtain an average value of 66.82, while the participation rate of support meperoleh average value of 55.37. At the level of participation of lecturers and officials to obtain support on average 59.36. The significance of the relationship between the level of support for SDL and the level of participation in the student receives a grade Pearson Moment 0.210. Comparison between the institutions (professors and official) and students associated with the level of participation of support found dissatisfaction tendency of students to support, and aspects of library facilities that do not have optimal functioning, as well as the construction of learning that do not provide autonomy to students. Keywords : self-directed learning (SDL), the participation of institutional support